High PINCH1 Expression in Human Laryngeal Carcinoma Associates with Poor Prognosis. (20th March 2018) - Tsinias, Georgios; Nikou, Sofia; Papadas, Theodoros; Pitsos, Panagiotis; Papadaki, Helen; Bravou, Vasiliki
Abstract : Focal adhesion signaling to actin cytoskeleton is critically implicated in cell migration and cancer invasion and metastasis. Actin-binding proteins cofilin and N-WASP regulate actin filament turnover, and focal adhesion proteins parvins and PINCH mediate integrin signaling to the actin cytoskeleton. Altered expression of these proteins has been implicated in human cancer. This study addresses their expression and prognostic significance in human laryngeal carcinoma. Protein expressions of cofilin, N-WASP, α -parvin, β -parvin, and PINCH1 were examined by immunohistochemistry in 72 human laryngeal squamous cell carcinomas. Correlations with clinicopathological data and survival were evaluated. All proteins examined were overexpressed in human laryngeal carcinomas compared to adjacent nonneoplastic epithelium. High expression of PINCH1 was associated significantly with high grade, lymph node-positive, and advanced stage disease. Moreover, high PINCH1 expression significantly associated with poor overall and disease-free survival and high cytoplasmic PINCH1 expression was shown by multivariate analysis to independently predict poor overall survival. In conclusion, we provide novel evidence that focal adhesion signaling to actin cytoskeleton is implicated in human laryngeal carcinogenesis and PINCH1 has prognostic significance in the disease.